Effect of Cyber-Golfing on Balance Amongst the Elderly in Hong Kong: A Pilot Randomised Trial - Daniel H.K. Chow; Stephen K.F. Mann (Hong Kong Journal of Occupational Therapy, 2015)
Background/Objective: Recent evidence showed that golf can develop balance amongst the elderly. This study aimed at evaluating if exergaming, in particular cyber-golfing, can be a feasible and inexpensive alternative to this valuable exercise. Methods: Twenty healthy community-dwelling elderly were recruited, and they were randomly assigned to either the experimental group (n = 10) or the control group (n = 10). Daily cyber-golfing training for 2 weeks was assigned to the participants of the experimental group, where regular table games with equal lengths and durations were arranged for the control group. Results: The results revealed that the participants in the experimental group showed significantly better post-training performances in the functional-reach test, F(2,17) = 5.16, p = .04, and single-leg-stance test, F(2,17) = 5.32, p = .03, than those in the control group. Conclusion: The results of this study suggest that cyber-golfing might be an alternative to golfing, which is capable of enhancing balance ability amongst community-dwelling elderly. The potential of exergaming as a clinical tool for geriatric rehabilitation was discussed.